Por la Ruta del Discurso Eurocéntrico en el Cine de Exploradores On the Path of Eurocentric Discourse in the Cinema of Explorers - Mónica Villarroel (Aisthesis, 2010)
El cine de exploradores en la época silente constituye un discurso sobre Latinoamérica construido desde una lógica eurocéntrica, reproduciendo relaciones de poder donde pueden identificarse rasgos de una colonialidad que, por una parte, enfatiza la modernidad y el progreso y, por otra, resalta las características de exotismo, minusvalía y precariedad de las culturas indígenas locales. Este artículo revisa un conjunto de producciones cinematográficas de exploradores europeos sobre América, a inicios del siglo XX, que evidencian esta perspectiva. Se detiene en un análisis exhaustivo del filme Tierras Magallánicas, del salesiano Alberto de Agostini, dialogando con otras producciones de similar periodo. The films made by European explorers, in the silent film era, are built on a Eurocentric logic when it comes to Latin America. They reproduce the relationships of power identifying, on the one hand, certain features of colonialism that emphasize modernity and progress, and, on the other hand, highlighting the characteristic exoticism, disability and the precariousness of the local indigenous cultures. The following article will review a number of films by European explorers on America from the early twentieth century, as a support to this perspective. It will conclude with a comprehensive analysis of the film Tierras Magallánicas, from the Salesian Alberto de Agostini, interwoven with other film productions from a similar period of time.